Three-Dimensional EncCon Tree - Huang, Mao Lin; Nguyen, Quang Vinh; Lai, Wei; Huang, Xiaodi (CGIV'07: Proceedings of the Computer Graphics, Imaging and Visualisation, 2007)
This paper describes a three-dimensional extension of a enclosure+connection layout technique, called EncCon tree. The three-dimensional visualization includes layout and navigation. The layout algorithm directly generalizes the two-dimensional EncCon tree layout algorithm to three-dimensional space in which nodes at the same level of the hierarchy are placed onto the same plane. The interactive navigation uses standard three-dimensional viewing techniques which include view transformation, rotation and zoom.